Automated control programs for characterizations of quantum cascade lasers. - Phann Sophearin. (2012)
In this Final Year Project, some LabVIEW programs were developed in order to automatically control the experimental instruments used for characterizing the quantum cascade laser (QCL) devices. QCL is a semiconductor laser which typically emits in the mid- to far-infrared and THz region of the electromagnetic spectrum. While the typical interband semiconductor lasers emit electromagnetic radiation through the recombination of electron-hole pairs across the material bandgap, the QCLs are unipolar with its emission being achieved through the use of intersubband transitions in a repeated stack of semiconductor multiple quantum well heterostructure.The purpose of the automation control programs is to make the process of this device characterization more efficient and accurate and consume less time as compared to the conventional, manual characterization where automating instrument control is not available. The programs were developed using National Instruments’ LabVIEW 2009 application, a graphic-based programming environment widely used for instrument control. Three main control programs were developed in this project; two of them are for the Power-Current-Voltage (L-I-V) characteristics with two different types of pulse generator, while the other one is for the far-field characteristics of the QCL device.